Nutritional Status And Post-cardiac Surgery Outcomes: An Updated Review With Emphasis On Cognitive Function - Norsham Juliana Nordin; Nur Adilah Shuhada Abd Aziz; Sofwatul Mokhtarah Maluin; Noor Anisah Abu Yazit; Sahar Azmani; Suhaini Kadiman; Kamilah Muhammad Hafidz; Nur Islami Mohd Fahmi Teng; Srijit Das (MDPI, 2024)
Indexed by WOS/Scopus/ERA